CHALLENGES OF TRANSLATING FRENCH IDIOMS INTO UZBEK: LINGUISTIC AND CULTURAL PERSPECTIVES - Akromova Farizod Nuriddinovna (International Journal of Literature and Language Studies, 2026)
The translation of idiomatic expressions remains one of the most complex tasks in translation studies due to the close relationship between language and culture. French idioms often contain cultural references, historical allusions, and figurative meanings that do not have direct equivalents in the Uzbek language. This study examines the linguistic and cultural challenges encountered in translating French idioms into Uzbek and explores the strategies used by translators to preserve meaning and communicative effect. The article highlights the importance of cultural competence, contextual understanding, and translation equivalence in achieving accurate and natural translations. The findings suggest that successful translation of idioms requires not only linguistic knowledge but also a deep understanding of the cultural backgrounds of both source and target languages [1–4].